Optimizing glucocorticoid therapy in congenital adrenal hyperplasia and analog conditions: the intersection of dose reduction, patient care, and coverage in the US - Khattab, Ahmed; Kim, Hyunwoo; Mulrooney, Mary; Leinwand, Brian; Hadker, Nandini; Cicero, Samantha; Cheng, Henry (Frontiers in Endocrinology, 2025)
BackgroundGlucocorticoid (GC) therapies treat many chronic conditions such as congenital adrenal hyperplasia (CAH), but long-term use carries risks of side effects (e.g., skeletal, cardiometabolic, mental health issues) that can negatively impact clinical and economic outcomes. Consequently, patients and providers seek to balance the lowest efficacious dose and side effect risk. To our knowledge, no research has analyzed US payer coverage decisions on medications that reduce GC reliance.ObjectiveTo understand the significance and implications of US payer perceptions and coverage/access decisions for therapies reducing GC doses, which may be of relevance to new therapies for CAH.MethodsA literature review was paired with primary market research to identify and characterize 5 GC-reducing therapies to evaluate payer coverage policies. No identified therapies were currently approved or studied in CAH. Qualitative interviews (n=13) were also conducted across managed care organizations, pharmacy benefit managers, and managed Medicaid payers to supplement publicly available information.ResultsGC-reducing therapies were desirable and therapeutically beneficial from payer perspectives based on market research of payer coverage policies; all therapies were covered in place of or in addition to GCs. Despite premium pricing vs. low-cost alternatives, all therapies evaluated were covered by some or all payers with prior authorization to label indication or trial criteria. Qualitative interviews revealed that payers clearly understood the clinical burden of long-term GC use; however, the economic burden was less understood. Payers stated that GC reduction is a secondary decision-making driver due to the focus on trial primary endpoints, contracting dynamics, lack of competitors, and small trial sample sizes. A subset of payers was interested in GC reduction data as a primary endpoint for rare diseases without treatment alternatives and in pediatric populations.ConclusionsDespite the premium price over GCs, GC-reducing therapies were covered in place of or in addition to GCs. Payers acknowledged the clinical value of reducing long-term GC use. Understanding what payers perceive as important criteria for coverage of GC-reducing medication may aid clinicians in evaluating utilization management criteria, such as step therapy, and increase access to medications aiming to reduce the patient burden associated with long-term GC use. This is particularly important in CAH where there is a high unmet need due to lifelong exposure to supraphysiologic doses of GCs.